Towards safer anti-inflammatory therapy: synthesis of new thymol-pyrazole hybrids as dual COX-2/5-LOX inhibitors - Mostafa M. M. El-Miligy; Ahmed K. Al-Kubeisi; Mohamed G. Bekhit; Saad R. El-Zemity; Rasha A. Nassra; Aly A. Hazzaa (Taylor & Francis Group, 2023)
New thymol − 1,5-disubstitutedpyrazole hybrids were synthesised as dual COX-2/5-LOX inhibitors. Compounds 8b, 8g, 8c, and 4a displayed in vitro inhibitory activity against COX-2 (IC50 = 0.043, 0.045, 0.063, and 0.068 µM) nearly equal to celecoxib (IC50 = 0.045 µM) with high SI (316, 268, 204, and 151, respectively) comparable to celecoxib (327). All target compounds, 4a-c and 8a-i, showed in vitro 5-LOX inhibitory activity higher than reference quercetin. Besides, they possessed in vivo inhibition of formalin-induced paw oedema higher than celecoxib. In addition, compounds 4a, 4b, 8b, and 8g showed superior gastrointestinal safety profile (no ulceration) as celecoxib and diclofenac sodium in the population of fasted rats. In conclusion, compounds 4a, 8b, and 8g achieved the target goal. They elicited in vitro dual inhibition of COX-2/5-LOX higher than celecoxib and quercetin, in vivo potent anti-inflammatory activity higher than celecoxib and in vivo superior gastrointestinal safety profile (no ulceration) as celecoxib.